Prospects for breeding agronomically superior Musa with resistance or tolerance to BSV - Tenkouano, A.; Hughes, J.; Dahal, G.; Pillay, M. (2003)
The genetic improvement of banana and plantain has focused on breeding for resistance to black sigatoka. This has been quite successful, but the distribution of improved hybrids has been impeded by the outbvreak of Banana streak virus (BSV). Integration of viral sequences in Musa genomes make it difficult to apply commonly accepted principles for host-plant resistance. The short-term strategy of breeding programs at IITA was to address the BSV issue through a practical approach based on identification of genotypes with low expression of BSV symptoms and low concentration of BSV antigenes under natural field conditions. Also, alternative plant propagation methods to reduce the incidence of BSV upon field establishment of seedlings were investigated. The longer term strategy involves ploidy and genome manipulation to reduce the probability for transcriptional recombination of BSV sequences dispersed in the Musa genomes thereby reducing the propensity for BSV expression in improved hybrids.